Ergonomics for well-being - a review - Hamid, Nur Suraya Sahol; Abdul Jalil, Nawal Aswan; Samin, Razali; Ismail, Muhammad Firdaus (Global Academic Excellence (M) Sdn Bhd, 2024)
This article examines the numerous Ergonomics studies conducted in various fields, with a primary emphasis on preventing accidents as well as incidents that could result in ergonomic and human factors issues for industrial workers. Researchers have discovered several technologies that can be used to enhance ergonomic treatments and reduce the frequency of incidents. Despite the fact that safety has a significant impact on human parts and ergonomics, this article bases its discussion on the various industrial zones. Following that, the workplace can clearly execute mitigation and prevention strategies. The environment and comfort level zones are interconnected in a workplace that handles machinery. Ergonomics are important human factors, particularly in the manufacturing sector. This paper examined several approaches put forth by different industries, considering the difficult frequencies and postures associated with each occupational activity. Note that various comfort level zones that relate to the workers are defined by each study tool. On the basis of this, only further research was done, and the prior literature thoroughly identified the issues.